PENGARUH MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN APLIKASI EDUCANDY TERHADAP KEMAMPUAN MENULIS PUISI PADA KELAS VIII SMP MUHAMMADIYAH 1 MEDAN TAHUN AJARAN 20252026 - Viva El Kahfi; Naelofaria, Salmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Make a Match learning model assisted by the Educandy application on the poetry writing ability of eighth-grade students at SMP Muhammadiyah 1 Medan in the 2025/2026 academic year. The research method used was an experimental method with a Two Group Post-test Only Control Design. The population of this study consisted of 66 students, divided into 33 students in the control class and 33 students in the experimental class. The control class used the Snowball Throwing learning model assisted by the Wordwall application, while the experimental class used the Make a Match learning model assisted by the Educandy application. The data collection technique was conducted through a poetry writing test based on assessment aspects including lines, stanzas, rhyme, imagery, diction, and figurative language.The results of the study showed that the average poetry writing ability in the control class was 65.72, categorized as fair, while the experimental class obtained an average score of 84.15, categorized as good. The normality test results indicated that both data sets were normally distributed, with the Lcount value of the control class being 0.152 and the experimental class being 0.140, both smaller than the Ltable value of 0.154. The homogeneity test result obtained a significance value of 0.260 > 0.05, indicating that the data were homogeneous. Furthermore, the hypothesis test result showed that tcount was -11, smaller than ttable -10, so H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Make a Match learning model assisted by the Educandy application has a significant effect on the poetry writing ability of eighth-grade students at SMP Muhammadiyah 1 Medan.